Government Policies and Sharia Economic Instruments in Advancing Green Economy Development in Indonesia - Masrukhan Masrukhan; Moh. Imron Rosidi; Arvy N. Osma (International Forum of Researchers and Lecturers, 2024)
This research investigates the integration of Sharia economic instruments into green economy policies in Indonesia, focusing on how these instruments can enhance sustainability efforts. Specifically, it evaluates the role of Green Sukuk, zakat, and waqf in supporting sustainable development projects. Sharia economic instruments are identified as essential tools for financing environmentally friendly projects while aligning with social and ethical values. The research explores how these instruments contribute to the green economy by expanding funding sources, increasing public participation, and promoting social welfare. The study finds that the hybrid approach of integrating Sharia instruments with green policies leads to more sustainable outcomes compared to secular-only frameworks. The integration fosters long-term stability, attracts ethical investors, and supports social inclusion, making green initiatives more resilient. This research highlights the potential of Sharia-compliant financing in advancing the Sustainable Development Goals (SDGs) and fostering a more inclusive and sustainable economic model. Recommendations are made for the Indonesian government to develop policies that incorporate Sharia instruments into the green economy framework to enhance financial support and community engagement.